The Local Wisdom Management of Non-Timber Forest Products of Bamboo plants by Batulaya people in Kecamatan Tinambung Kabupaten Polewali Mandar - Ahmad Ahmad; Andi Ridha Yayank Wijayanti; Qaisar Qaisar; Muhammad Sarif; Muhammad Arafat Abdullah (Universitas Andi Djemma Palopo, 2023)
Local wisdom is part of a society's culture which has values, norms, and is usually passed down from generation to generation through stories and knowledge that develops in society. This research aims to examine the forms of local wisdom of the Batulaya Village community in managing bamboo plants. This type of research is qualitative which uses several informants to conduct interviews with a triangulation approach. There are two sources of data used, namely primary data including information obtained directly through the respondent interview process and secondary data including journal or article references. The results of the research show that on 1 (Muharram) it is not permissible to plant bamboo, in maintaining bamboo plants there are